Molecular Study on Twin Cohort with Discordant Birth Weight - Payal Chakraborty; Hajnalka Orvos; Edit Hermesz (MDPI AG, 2023)
The increased rate of twinning has pointed out newer challenges in clinical practices related to gestational complications, intrauterine growth restriction, perinatal mortality, and comorbidities. As a twin pregnancy progresses, the increased demand for oxygen supply can easily disrupt the redox homeostasis balance and further impose a greater challenge for the developing fetuses. A substantial birth-weight difference acts as an indicator of a deficit in oxygenation or blood flow to one of the fetuses, which might be related to a low bioavailable nitric oxide level. Therefore, in this study, we focused on networks involved in the adjustment of oxygen supply, like the activation of inducible and endothelial nitric oxide synthase (NOS3) along with free radical and lipid peroxide formation in mature twin pairs with high birth-weight differences. The selected parameters were followed by immunofluorescence staining, fluorescence-activated cell sorting analysis, and biochemical measurements in the umbilical cord vessels and fetal red blood cells. Based on our data set, it is clear that the lower-weight siblings are markedly exposed to persistent intrauterine hypoxic conditions, which are connected to a decreased level in NOS3 activation. Furthermore, the increased level of peroxynitrite aggravates lipid peroxidation and induces morphological and functional damage and loss in redox homeostasis.